Escritura do espaço na música eletroacústica - Alveskog, George Olof de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Esta pesquisa tem como principal objetivo elucidar como a estruturação espacial dos sons tem sido utilizada como uma importante estratégia de composição em obras eletroacústicas acusmáticas. Para isso, serão analisadas obras e escritos de alguns dos compositores que mais contribuíram para o assunto, apresentando tanto problemáticas gerais decorrentes da inserção do espacialidade na escritura musical, como técnicas de elaboração da espacialidade encontradas durante as análises das obras.

The main purpose of this research is to shed light on how the spatial structuring of sounds has been utilized as an important compositional strategy on electroacoustic acousmatic pieces. For this purpose, compositions and writings from some of the main composers which have contributed to the subject will be analyzed, presenting both the general problematics occasioned by the insertion of spatiality in the musical thinking and elaborative process and the spatial elaborative techniques found during the analyses of the compositions.
Spatial structuring processes in electroacoustic music
Keywords: Música eletroacústica; Escritura musical; Composição musical; Espaço sonoro; Espacialidade sonora; Electroacoustic Music; Musical thinking and Elaborative!process; Musical Composition; Sound Space; Musical Spatiality